Screw Joint Stability in Conventional and Abutment-Free Implant-Supported Fixed Restorations - Scherg, Stefan; Karl, Matthias (International Journal of Prosthodontics, 2016)
Procera Implant Bridges (PIBs) do not engage supporting implant shoulders and are fixed using comparably long retention screws. The aim of this in vitro clinical study was to determine the detorque values in PIBs and conventionally fabricated fixed dental prostheses (FDPs).Two groups of screw-retained implant-supported three-unit FDPs (n=10) were fabricated by means of conventional casting or computer-aided design/computer-assisted manufacture to fit an in vitro situation with two implants. Following fixation, the restorations were subjected to masticatory simulation (100,000 cycles, 100 N) and subsequent detorquing of the retention screws. In the clinical part, a total of 10 patients received PIB restorations in the premolar/molar region that were detorqued after 2, 4, and 6 months. One-sample t tests adjusted for multiple testing by the Bonferroni-Holm method were applied for statistical analysis based on percentage detorque values (?=.05).60% of the initial torque values were maintained in screws directly retaining restorations, while the abutment screws used in the conventional restorations showed detorque levels in the range of 80%. No significant difference in detorque levels between screws retaining PIBs and conventional FDPs could be detected (P=.5186). The abutment screws showed significantly greater detorque values compared with screws directly retaining restorations (P=.0002; P=.0000). In vivo, a significant increase in detorque values ranging from 21.64 Ncm after 2 months to 27.81 Ncm after 6 months was recorded.Prosthetic screws retaining implant-supported FDPs show torque loss during the initial period of service. Retightening reduces the amount of future torque loss.
EVALuna2:24827